KOMUNIKASI INSTRUKSIONAL PELATIH MARCHING BAND DALAM MENINGKATKAN KEMAMPUAN PENGGUNAAN ALAT MUSIK DI SEKOLAH DASAR NEGERI 106 RUMBAI PEKANBARU - Ginting, Ivory Karina; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Marching band at the 106 Rumbai Pekanbaru Public Elementary School is a program whose purpose is to develop and grow the character and musical abilities of existing students. Fostering and training elementary school students is not an easy matter, because they are still very young and have never played musical instruments before. The students just learned about musical instruments after they joined the marching band and after joining they gained sufficient expertise in playing musical instruments. The purpose of this study was to determine the credibility of the SDN 106 marching band coach, the assessment of entering behavior by the trainer, the method used and the communication barriers that occurred during the SDN 106 marching band training process. This study used qualitative research methods. The research was conducted at the 106 Rumbai Pekanbaru Elementary School. Informant selection is done by porposive techniques. Data collection techniques consist of observation, interviews, and documentation. Data analysis techniques use descriptive analysts according to Huberman and miles. for the validity checking technique the data used in this study is the Extension of participation, Triangulation and Adequacy of references. The results of the study show that the credibility of the marching band coaches is very adequate to foster and train students, it can be seen from the skills and skills of the trainers in playing a number of musical instruments, and also from the trainer's ability to teach the members of the marching band with great skill so the coach gets the trust of his members. The trainer also applies the initial behavioral assessment used to streamline and direct the students according to the interests, talents and abilities of the students, so that students can be nurtured in the place that best suits them. The methods used by trainers in teaching and improving the abilities of students are varied, including the command method, demonstration method, training method,  discussion and question and answer method and also practice with friends. Then there are three types of obstacles,  from the communicator, such as the use of complex language, obstacles on the channel, damaged tools and unsupportive weather and obstacles on Communicating, communicant that is not focused and causes noise so learning becomes disturbed.